A revision of the genus Podaena Ordish (Insecta: Coleoptera: Hydraenidae) - Delgado, Juan A.; Palma, Ricardo L. (Zootaxa, 2010)
The New Zealand endemic genus Podaena Ordish, 1984 is revised. Eleven species are recognized of which four are described as new, and the remainder redescribed. The new species are: Podaena aotea from Great Barrier Island, Podaena hauturu from Little Barrier Island, Podaena mariae from the west coast of the South Island, and Podaena moanaiti from Lake Waikaremoana. The most useful characters to separate species are the shape of the maxillary palps and the shape and chaetotaxy of the foretibiae in males; these characters are illustrated for all the species. Unlike most genera of Hydraenidae, male genitalia in Podaena are not diagnostic for all species. The known geographical distribution of some species is expanded, and the complete collecting data for the type series of all the species described by Ordish (1984) are given, together with distribution maps.